2013
DOI: 10.1016/j.actpsy.2013.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Disgust- and not fear-evoking images hold our attention

Abstract: Even though disgust and fear are both negative emotions, they are characterized by different physiology and action tendencies. The aim of this study was to examine whether fear- and disgust-evoking images would produce different attention bias effects, specifically those related to attention (dis)engagement. Participants were asked to identify a target which was briefly presented around a central image cue, which could either be disgusting, frightening, or neutral. The interval between cue onset and target pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
92
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 32 publications
8
92
1
1
Order By: Relevance
“…Recent reports however suggest that stimuli evoking disgust produce different attention effects than those eliciting fear, even when these stimuli are equally arousing and similarly negative (Carretié, Ruiz-Padial, López-Martín, & Albert, 2011;Chapman, Johannes, Poppenk, Moscovitch, & Anderson, 2013;Van Hooff et al, 2013). More specifically, results from these studies suggest that attention bias effects are exclusively present or are much larger for disgustas compared to fear-evoking pictures.…”
mentioning
confidence: 79%
See 3 more Smart Citations
“…Recent reports however suggest that stimuli evoking disgust produce different attention effects than those eliciting fear, even when these stimuli are equally arousing and similarly negative (Carretié, Ruiz-Padial, López-Martín, & Albert, 2011;Chapman, Johannes, Poppenk, Moscovitch, & Anderson, 2013;Van Hooff et al, 2013). More specifically, results from these studies suggest that attention bias effects are exclusively present or are much larger for disgustas compared to fear-evoking pictures.…”
mentioning
confidence: 79%
“…For example, in our previous study we found that task irrelevant disgust-evoking pictures delayed subsequent, peripheral target identification exclusively when these targets were presented 200 ms after picture onset and not after 500, 800, or 1100 ms (Van Hooff et al, 2013). Likewise, Ciesielski, Armstrong, Zald, and Olatunji (2010) reported that the enhanced attentional blink effect for emotional stimuli rapidly declined from short (200 ms) to longer time lags (400 ms and 600 ms) and even reversed for the longest time lag of 800 ms (i.e., enhanced instead of diminished target processing following negative images).…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…),这些研究为无意识认知控制的存在提供了直接的实验证据。 情绪对反应抑制的影响一直以来都是研究的热点,有研究表明,与任务无关的情绪图片会消耗注意 资源,从而阻碍反应抑制的表现 (De Houwer & Tibboel, 2010;Hartikainen, Siiskonen & Ogawa, 2012;Lindstrom & Bohlin, 2012;Verbruggen & De Houwer, 2007);也有研究表明,情绪刺激能够促进反应抑制 的表现 (Pessoa, Padmala, Kenzer et al, 2012;Robinson, Krimsky & Grillon, 2013 (Carretie, Ruiz-Padial, Lopez-Martin et al, 2011;Krusemark & Li, 2011;Nicol, Perrotta, Caliciuri et al, 2013;Susskind, Lee, Cusi et al, 2008;van Hooff, Devue, Vieweg et al, 2013; Ver- 对阈下反应时做 3(中性、恐惧、厌恶)*2(go/no-go)的重复测量方差分析发现,两者交互作用不显著, F (2,21) = .678,p = .519;go/no-go 的主效应显著,F (2,21) = 9.504,p = .009,no-go 的反应时比 go 的反 应时要长。进一步分析表明,当情绪图片是中性时,出现了阈下的反应抑制,no-go 试次的反应时比 go 试次的更长,p = .06;当情绪图片是恐惧时,no-go 试次的反应时比 go 试次的更长,p = .047;而当情绪…”
unclassified